Slovnični spol prevzetih samostalnikov v knjižni slovenščini 16. stoletja - Legan Ravnikar, Andreja (Slavistična revija, 2019)
The article discusses the category of gender in nouns borrowed from or with the mediation of German in the sixteenth-century Slovene literary language. Despite the tendency of loanwords to retain their gender in the donor language, there are certain aberrations on which the analysis focused with the goal of discovering typological features and determining causes for the phenomena. In practical lexicographic work, morphological, syntactical, and semantic criteria are used to identify grammatical gender of lexemes.
Keywords: 16. stoletje; 16th century; Dictionary of the Slovene Literary Language; German as a donor language; grammatical gender; nemščina kot izhodiščni jezik; Slovar slovenskega knjižnega jezika; Slovenian language; slovenščina; slovnični spol; transmorfemizacija; transmorphemization